2008
DOI: 10.1021/ja710526r
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of Dynamical Transitions in a Soluble Protein and Its Hydration Water:  Direct Measurements by Neutron Scattering and MD Simulations

Abstract: The coupling between protein dynamics and hydration-water dynamics was assessed by perdeuteration, temperature-dependent neutron scattering, and molecular dynamics simulations. Mean square displacements of water and protein motions both show a broad transition at 220 K and are thus coupled. In particular, the protein dynamical transition appears to be driven by the onset of hydration-water translational motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
249
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(277 citation statements)
references
References 27 publications
27
249
1
Order By: Relevance
“…The deuterated MBP in H 2 O gave access to the dynamics of hydration water, which contributes 73% to the total incoherent scattering cross section but only 2% in natural abundance MBP in D 2 O. The MSD of water and protein motions, plotted in Figure 1A, are similar up to 220 K, at which temperature they both exhibit a transition 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deuterated MBP in H 2 O gave access to the dynamics of hydration water, which contributes 73% to the total incoherent scattering cross section but only 2% in natural abundance MBP in D 2 O. The MSD of water and protein motions, plotted in Figure 1A, are similar up to 220 K, at which temperature they both exhibit a transition 27 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, however, the onset of hydration water translational diffusion at 200 K, in a membrane, was not observed to trigger a dynamical transition in the membrane protein 25,26 , suggesting a more complex interaction between protein, water, and the membrane lipid environment. Recent neutron scattering studies, using specific deuterium labelling, confirmed that a dynamical transition coincides with the onset of hydration water translational diffusion, in the case of a soluble proteins 27 , but not in the case of a membrane protein 3,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The change in slope of the temperature dependence of hydrated protein's mean-square displacement around 220 K has been extensively studied, 9,11,13,23,24,67,68 as this transition is connected to protein function and vanishes in the absence of hydration. It has been proposed that the dynamical crossover around 220 K could be associated with a large scale structural change in hydrogen bond connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The steeper increase above 220-230 K is usually correlated with the so called dynamic transition, reflecting the increase in internal rotation and translation dynamics. 9,12,13,23,24,28,32 The hu 2 i values for a nominally dry sample (Fig. 1, inset) shows linear temperature dependence up to about 240 K, and a deviation from linearity above this temperature.…”
Section: Neutron Scatteringmentioning
confidence: 95%
“…These motions actually involve the atoms not just of the biological structure itself but also of the surrounding medium with which a coupling exists. Therefore, depending on the circumstances, the protein can be considered "slaved" or "sequestered" by the host medium which can be able to suppress its dynamics, so resulting in a retardation of denaturation processes or a slowing down of biological function [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%